1994
DOI: 10.1107/s0108768194003599
|View full text |Cite
|
Sign up to set email alerts
|

Structure of suberic acid at 18.4, 75 and 123 K from neutron diffraction data

Abstract: Neutron diffraction data for suberic acid [HOOC(CH2)6COOH] were collected at 18.4, 75 and 123 K using a twinned crystal. The neutron data reduction included derivation of a complete set of corrected intensities, as if from a single crystal. This was followed by full-matrix structure refinement in the usual way. The molecule has an almost fully extended conformation with the hydrocarbon chains packed in an orthorhombic mode. Molecules form infinite hydrogen-bonded chains with crystallographic inversion centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 10 publications
1
18
0
1
Order By: Relevance
“…No thermotropic phase transition has been reported so far, however, Terpstra et al (1993) and Kampermann et al (1995) demonstrated an intrinsic anharmonicity in the H atoms by re®ning the Gram±Charlier coef®cients (Johnson & Levy, 1974) from several X-ray and neutron diffraction measurements. Aliphatic dicarboxylic HOOC(CH 2 ) n À 2 COOH acids with 5 n 13 (Cn) crystallize in monoclinic space groups (Mortimer et al, 1958;Housty & Hospital, 1964, 1965a,b, 1966a,b,c, 1967Sintes et al, 1966;Housty, 1968;Haget et al, 1980;Gao et al, 1994;Bond et al, 2001a,b). The Cn structures show hydrogen-bonded arrangements forming ribbons extended throughout the crystal.…”
Section: Introductionmentioning
confidence: 99%
“…No thermotropic phase transition has been reported so far, however, Terpstra et al (1993) and Kampermann et al (1995) demonstrated an intrinsic anharmonicity in the H atoms by re®ning the Gram±Charlier coef®cients (Johnson & Levy, 1974) from several X-ray and neutron diffraction measurements. Aliphatic dicarboxylic HOOC(CH 2 ) n À 2 COOH acids with 5 n 13 (Cn) crystallize in monoclinic space groups (Mortimer et al, 1958;Housty & Hospital, 1964, 1965a,b, 1966a,b,c, 1967Sintes et al, 1966;Housty, 1968;Haget et al, 1980;Gao et al, 1994;Bond et al, 2001a,b). The Cn structures show hydrogen-bonded arrangements forming ribbons extended throughout the crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Suberic acid (COOH(CH 2 ) 6 COOH) is a fatty acid whose crystal structures were experimentally obtained at six different temperatures [20,21]. The starting structure for the MD simulation is shown in Fig.…”
Section: Methods and Modelmentioning
confidence: 99%
“…The following reflection conditions were observed: 0k00, k --2n, and hOlm, m = 2n, with the monoclinic axis b. Housty & Hospital, 1965;Gao, Weber & Craven, 1994). C, pp.…”
Section: Methodsmentioning
confidence: 99%